PENGARUH KEGIATAN EKSTRAKURIKULER TAHFIDZUL QURAN TERHADAP KUALITAS HAFALAN JUZ AMMA ANAK USIA 5-6 TAHUN DI RA RAUDLATUT TA"™LIM - Julia, Rosi; Yana, Medi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Being a child who memorizes the Koran at Raudlatut Taklim, which does not only focus on tahfidz activities, is not an easy thing. Because with various formal and informal educational activities, children must be able to manage a lot of time to deposit their memorization. And in order to develop potential and equip themselves, Raudlatut Ta'lim has a program of extracurricular activities that aims to support the learning process to run well and to form a more mature child's personality. All extracurricular activities are considered to be able to influence the quality of memorizing juz amma of children at ra Raudlatut Ta'lim. This type of research is quantitative research. This research was conducted with the aim of knowing the effect of extracurricular activities on the quality of memorizing juz amma of children at Raudlatut Ta'lim. The population in this study were all Raudlatut Ta'lim children, while the sample in this study consisted of 15 children. More than that, data analysis techniques use product moment, reliability with the "r" hypothesis table. The results of the product moment correlation with the "r" table of 5% and 1% significance were obtained that r_xy = 919 was greater than r_table, both at the significance level of 5% and 1% with a comparison formulation. It can be concluded that there is a positive influence between the effects of extracurricular activities on the quality of memorizing juz amma of children in ra Raudlatut Ta'lim.